Benefits and Difficulties in Using Learning Management System (LMS) in Paragraph Writing Class: A Study of a Lecturer’s and Her Students’ Perception - Muhammad Nurul Multazam; Chairil Anwar Korompot; Munir Munir (Journal of Excellence in English Language Education, 2022)
The objective of this research was to find out benefits and difficulties in using learning management system (LMS) in paragraph writing class: a study of a lecturer’s and her students’ perception.  This research employed a mixed method research called a convergent parallel mixed method design with qualitative and quantitative data. The population of this research were a lecture and 30 students from class A and 34 students from class B of English department at UNM in academic year 2019. The data were collected through questionnaire for the students and in-depth interview for the lecturer. The findings showed that the benefits of LMS perceived by the lecturer are it is complete, easy to use, has good features, effective to design the meetings and assignments, reducing the use of internet quota, and extensive time to do the task. While her difficulties are it is not socialized well, difficult to create a video, poor signal, and there is no feature for correcting paragraph writing. Meanwhile, the benefits of LMS perceived by the students are accessible material, well-organized, easy assignments submission, fun quiz, helpful video explanation, less paper, not time consuming, and improving skill in technology and punctuality. In contrast, their difficulties before Covid-19 pandemic are technical problem in paragraph writing, sometimes it was inaccessible due to bad network, and there was no enough credit for the internet. Likewise, their difficulties during Covid-19 pandemic are LMS was often error, cannot ask the lecturer directly, bad network to open the video, and sometimes it took the answers wrong even they are already correct. It is suggested that it is significant to preserve the benefits and overcome the difficulties in using LMS especially in paragraph writing class.